2017
DOI: 10.1186/s13018-017-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of arthroscopic surgery for external snapping hip

Abstract: BackgroundStudies have reported on the arthroscopic technique for release of external snapping hip syndrome. However, no study with large sample size has been reported for arthroscopic surgery.MethodsPatients with 229 bilateral and 19 unilateral external snapping hips were treated from January 2012 to June 2013. After locating the contracture position, arthroscopic surgery was performed accordingly. Preoperative and postoperative angles were compared.ResultsComparing range of motion, all patients obtained high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…There are a limited number of studies [ 6 , 9 , 13 , 15 , 16 ], which are usually retrospective, with inherent limitations in study design and sample size (Table 1 ). Although with several limitations, these studies showed that endoscopic techniques are safe and reproducible, and the outcomes are encouraging.…”
Section: Resultsmentioning
confidence: 99%
“…There are a limited number of studies [ 6 , 9 , 13 , 15 , 16 ], which are usually retrospective, with inherent limitations in study design and sample size (Table 1 ). Although with several limitations, these studies showed that endoscopic techniques are safe and reproducible, and the outcomes are encouraging.…”
Section: Resultsmentioning
confidence: 99%
“…No long-term postoperative complications were found and no infections, major swelling, hematomas, or wound dehiscence occurred in all of the four types of cases. All patients achieved good results after arthroscopic surgery [ 30 ]. For the 118 patients in our study, the GD scale was improved from 55.5 ± 10.6 before operation to 90.1 ± 5.2 at the last follow-up ( p < 0.05), and the satisfaction rate was up to 95.8%.…”
Section: Discussionmentioning
confidence: 99%
“…However, Huang et al [ 3 ] have found that surgical release of GMC can significantly reduce the tilt and lateral shift of the patella by comparing preoperative and postoperative knee CT images. Additionally, multiple studies [ 3 , 5 , 9 , 12 , 35 , 36 ], from the functional and symptomatic perspective, have shown that early surgery effectively reduces patient symptoms and improves the quality of life, with high patient follow-up satisfaction. It is reasonable to assume that early diagnosis and surgery are beneficial to patients, while it also needs to be validated by further studies based on comparison of preoperative and postoperative radiographic parameters of AP pelvic radiograph.…”
Section: Discussionmentioning
confidence: 99%